Genome wide association studies in yam reveal the challenge of high heterozygosity - Agre, A.P.; Darkwa, K.; Kohtaro, I.; Matsumoto, R.; Asfaw, A. (2025)
Yam (Dioscorea spp.) is a herbaceous vine crop valued for its starchy tubers, which are rich in essential nutrients. Its genome is highly heterozygous, contributing to considerable genetic diversity and adaptability. Understanding the polymorphism information content (PIC) of genetic markers is critical for enhancing key agronomic traits such as yield. In this study, we conducted a genome-wide association analysis that accounts for heterozygosity to investigate fresh tuber yield variation in white Guinea yam (Dioscorea rotundata Poir). A total of 173 genotypes including 86 elite breeding clones, 77 genebank accessions, and 10 farmer varieteies were genotyped through whole-genome resequencing, yielding approximately 1.6 million single nucleotide polymorphism (SNP) markers. Association analysis was performed using a multi-locus mixed linear model (MLM), incorporating kinship matrices derived from marker subsets grouped by PIC levels (≤ 0.1, 0.1–0.2, 0.2–0.4, and > 0.4), alongside population structure. The analysis revealed that high-PIC markers had greater influence on trait associations. Twelve stable SNPs were significantly associated with fresh tuber yield. Functional annotation of these markers revealed putative genes related to plant growth and cellular regulation. Notably, markers located in heterozygosity-rich genomic regions were linked to high-yielding genotypes, while those in homozygous regions were associated with lower yields. These findings underscore the potential of PIC-based marker selection and highlight the value of integrating heterozygosity metrics into genomic-assisted breeding strategies for improving fresh tuber yield in white Guinea yam.